Using the Patient Health Questionnaire (PHQ-9) and the Edinburgh Postnatal Depression Scale (EPDS) to assess suicidal ideation among pregnant women in Lima, Peru. - Zhong, Qiu-Yue (2015)
We sought to examine the concordance of two suicidal ideation items from the Patient Health Questionnaire-9 (PHQ-9) and the Edinburgh Postnatal Depression Scale (EPDS), to evaluate the prevalence of suicidal ideation among pregnant women, and to assess the co-occurrence of suicidal ideation with antepartum depressive symptoms. A cross-sectional study was conducted among 1,517 pregnant women attending prenatal care clinics in Lima, Peru. Item 9 of the PHQ-9 assesses suicidal ideation over the last 14 days while item 10 of the EPDS assesses suicidal ideation in the past 7 days. The two suicidal ideation items have a high concordance rate (84.2 %) but a moderate agreement (the Cohen's kappa = 0.42). Based on the PHQ-9 and the EPDS, 15.8 and 8.8 % of participants screened positive for suicidal ideation, respectively. Assessed by the PHQ-9, 51 % of participants with suicidal ideation had probable depression. In prenatal care clinics, screening for suicidal ideation is needed for women with and without depressive symptoms. Future studies are needed to identify additional predictors of antepartum suicidality, determine the appropriate duration of reporting period for suicidal ideation screening, and assess the percentage of individuals with positive responses to the two suicidal ideation items at high risk of planning and attempting suicide.